Pengaruh Pelatihan Kerja Terhadap Kinerja Karyawan Yang Dimediasi Kemampuan Kerja - Mardi Astutik; Nur Hilal (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2021)
This study aims to determine and analyze the effect of promotion and service quality on the decision to choose. The variables in this study are Promotion and Service Quality and Decision to Choose which can solve the problems experienced by PT. Pegadaian (Persero) East Palu Branch. The findings in the study show that the value felt by customers is still low, if the results of the interview are associated with the mean value obtained in the questionnaire which shows that it is still low. on the contrary, when based on the results of the t-count and the P-value, it does not mean that the results are better, in this case the PT. Pengadaian (Persero) Palu Timur Branch needs to increase its sales promotion and dimensions of service quality more intensely and touch the hearts of customers by frequently providing information about pawnshop products through social media, one of which is WhatsApp. This study uses a survey research design and is verification in nature. The data source is primary data, namely data collected through questionnaires and documentation studies related to this research. The analysis method used is multiple linear regression analysis. The results showed that simultaneously promotion and service quality had a significant effect on decision making with an R Square value of 0308 or 308%.